2010
DOI: 10.1292/jvms.10-0271
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Antimicrobial Susceptibility of Brachyspira hyodysenteriae Strains Isolated in Japan from 1985 to 2009

Abstract: ABSTRACT. The antimicrobial susceptibilities of 72 Brachyspira hyodysenteriae isolates collected from clinical cases of swine dysentery (SD) in 11 prefectures in Japan between 1985 and 2009 were investigated by an agar dilution method using five antimicrobial agents. There is a tendency of Japanese field isolates of B. hyodysenteriae to acquire resistance to the main antimicrobials used in SD treatment such as tiamulin, valnemulin, and efrotomycin. A responsible approach for selection and use of antimicrobial … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
13
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 13 publications
(14 reference statements)
4
13
0
Order By: Relevance
“…Also macrolides (tylosin and, more recently, tylvalosin) and the closely related lincomycin (lincosamide) have been commonly included in SD therapeutic strategies [5] (Table 1). However, the emergence of B. hyodysenteriae strains with reduced susceptibility to one or more of these antibiotics and the presence of genetically diverse multiresistant isolates has been confirmed in several countries [90,91,92,93,94,95,96,97,98]. This fact complicates treatment and control of SD and should alert veterinary surgeons and pig farmers for the need of a strategic approach to select antibiotics, which must only be used on strict indications following proper field and laboratory diagnosis in order to guarantee their long-term efficiency for SD treatment.…”
Section: The Fight Against Sdmentioning
confidence: 99%
“…Also macrolides (tylosin and, more recently, tylvalosin) and the closely related lincomycin (lincosamide) have been commonly included in SD therapeutic strategies [5] (Table 1). However, the emergence of B. hyodysenteriae strains with reduced susceptibility to one or more of these antibiotics and the presence of genetically diverse multiresistant isolates has been confirmed in several countries [90,91,92,93,94,95,96,97,98]. This fact complicates treatment and control of SD and should alert veterinary surgeons and pig farmers for the need of a strategic approach to select antibiotics, which must only be used on strict indications following proper field and laboratory diagnosis in order to guarantee their long-term efficiency for SD treatment.…”
Section: The Fight Against Sdmentioning
confidence: 99%
“…In B. hyodysenteriae of porcine origin, widespread resistance has emerged to tylosin in the USA, Denmark, Australia, Finland, Belgium, Sweden and Spain (Kinyon & Harris, 1980;Rønne & Szancer, 1990;Smith et al, 1991;Hommez et al, 1998;Honkanen-Buzalski & Huovinen, 1999;Bengtsson et al, 2010;Hidalgo et al, 2010). Tiamulin resistance has been described in recent years from Hungary, the UK, the Czech Republic, Germany, the Netherlands, Spain and Japan (Molnár, 1996;Gresham et al, 1998;Lobova et al, 2004;Rohde et al, 2004;Duinhof et al, 2008;Hidalgo et al, 2010;Ohya & Sueyoshi, 2010). Compared with the situation in pigs, there is little information on antimicrobial susceptibility in Brachyspira spp.…”
Section: Introductionmentioning
confidence: 99%
“…Valnemulin has been used extensively to treat respiratory tract infection in swine, calf and poultry (Stipkovits et al ., ; Tzika et al ., ; Jansson & Pringle, ). Previous studies showed that valnemulin had great antibacterial activities against mycoplasma, spirochetes, gram‐positive bacteria, and some fastidious gram‐negative bacilli (Karlsson et al ., ; Ohya & Sueyoshi, ). Mycoplasma gallisepticum was more susceptible to valnemulin when compared to enrofloxacin, tylosin, lincomycin/spectinomycin, and tiamulin (Jordan et al ., ; Verlinden et al ., ).…”
Section: Introductionmentioning
confidence: 99%